Autonomy, Fairness and Active Relationships: Children's Experiences of Well‐being in Childcare. (14th October 2018) - Cooke, Emma; Brady, Michelle; Alipio, Cheryll; Cook, Kay
Abstract : Researchers and policy‐makers are increasingly concerned with children's well‐being in Early Childhood Education and Care (ECEC) and Outside School Hours Care (OSHC) settings. Recent research identifies the value of using qualitative methods to understand children's experiences of well‐being in ECEC/OSHC, but there remain few such studies. This article presents findings from a child‐centric qualitative study with Australian children of nurses and police, which sought to understand their experiences of well‐being in ECEC/OSHC. Children's experiences of well‐being were shaped by parental relationships, how informed they were about the rationale for their care arrangements and the degree of age‐appropriate autonomy they experienced.